Jejunal inflammatory myofibroblastic tumor: a rare entity - Chaudhary, Tarun; Singh, Santosh Kumar; Harsh, Meena (International Surgery Journal, 2017)
Inflammatory myofibroblastic tumor is one of the rare solid tumor occurring in children. Main stay of treatment is surgical resection and in some corticosteroids or NSAIDS may be useful. Here, a case of 3-year-old female with inflammatory myofibroblastic tumor of jejunum is presented, that was evaluated clinically, investigated radiologically and finally histopathology confirmed the diagnosis. No complications occurred at peri and postoperative period. The patient was on regular follow-up and no recurrence had been documented yet in 1 year of follow up. In this article, we reviewed the literature for inflammatory myofibroblastic tumor.